Effective graphics in structures class integrating structures into architecture - Dytoc, Bronne C. (2009)
This paper focuses on alternative teaching methods of illustrating structural behavior and concepts for integration into architectural design thinking. To reach this state, th pedagogic gap between architectural and structural classes needs to be bridged. The teaching methods are based on two viewpoints: 1) To comprehend structures in a graphical manner, and 2) To understand strucutres as a potent sculptor of form.

Keys to effectively teaching structures to an architectural class are to communicate with graphics, drawings, demonstration models, and familiar languages. These keys are employed for topics such as stress-strain, shear-moment diagrams, beam-column shapes, Maxwell truss diagrams, Polygonal Force diagrams from daily life further clarify and demystify structures, integrating it into architectural language and experience. Subsequent computations follow to appreciate comparative solutions, and materials and construction issues. The formulae variables are recognized as tools for shaping structural-architectural elements. Furthermore, architectural cases are analyzed in a series of slide lectures, revealing the variety of dynamic forms generated from structural issues. Finally, bridge or tower models are built and tested to realize the three-dimensional aspect of structural behavior. To help validate these methods and ideas to the reader, the paper shall be more graphical than textual.

The effectivity of these alternative methods are manifested in projects of later design studios, and are also noted in student evaluations of the structural class.